First, notice that 9 = 3^{2}^{. }Then the term on the left can be rewritten as (3^{2})^{x}. Using the rules of powers, that becomes 3^{2x}.

The term on the right is already a power of 3 -- there, the power is x^{2} - 4x.

Since both sides are expressed as powers of 3, you can ignore the 3 and set the exponents equal to each other.

We have: 2x = x^{2} - 4x

We can rearrange this into a quadratic equation: x^{2} - 6x = 0, or

x(x - 6 ) = 0

Setting each factor equal to 0, we get:

**x = 0 or x = 6**